IMPLEMENTASI METODE K-MEANS CLUSTERING UNTUK MENENTUKAN PERSEDIAAN STOK BARANG PADA TOKO AT-THULLAB TUBAN - Ghofur, Muhammad Abdul; Zayn, Afta Ramadhan; Faila, Rizka Nur (Al-Mantiq, 2024)
The At-Thullab store is an office stationery (ATK) store that sells various kinds of office stationery needs and several other types of goods such as pens, books, pencils, children's toys, and some birthday supplies. The At-Thullab store sells a variety of stationery among the community in the Sumurcinde Village area, Soko District, Tuban Regency. In handling stationery sales services, the At-Thullab store has one employee to serve the needs of its own buyers. In sales transactions there are many buyers who make transactions every month. There are so many types of goods it is not known which goods are most interested in buyers, so sometimes there are stockpiles of goods that are of less interest to buyers. In this study, k-means clustering was applied in determining clustering on item data in the At-Thullab store . Determination of inventory stock that can be accessed through web-based k-means clustering can be used as a support or complement for shop owners, shop heads and store employees, at At-Thullab stores. With these results, the store can also consider which products will be introduced to the store with the most sales. In this study, it can be concluded that several things are needed to analyze sales that occurred at the At-Thullab Store on January 1 – March 20 2023. The data was processed using k-mean clustering to determine groups of goods that did not sell well, sold and those that were very salable in this study the.